2021
DOI: 10.21931/rb/2021.06.01.19
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Moniliophthora roreri isolates from selected morphology groups in harvested cacao pods and in vitro sensitivity to compost tea.

Abstract: Moniliopthora roreri is the frosty pod rot disease (FPD) and one of the most devastating cacao pathogens worldwide. However, M. roreri pathogenicity on harvested cacao pods and sensitivity to compost tea have not been fully described. Monosporic cultures of M. roreri from different morphology groups were obtained. The isolates’ pathogenicity was tested by inoculation onto harvested cacao pods, and symptoms were evaluated at 3-day intervals during 16 days before estimating the area under the disease progress cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The typical symptoms include abnormal shoots that display stem swellings, bud proliferation, and vegetative brooms, which inspired the name witches’ broom disease in cocoa [ 5 ]. The results of recent studies from the major cocoa-producing provinces of Ecuador showed that Moniliophthora species possess high morphological and genetic diversity [ 6 , 7 , 8 , 9 ]. For this reason, some alternatives such as cacao agroforestry systems [ 1 ] and biological controls using products based on endophytic organisms, including the combined application of natural or chemical products [ 10 ], have been used to reduce the impact of diseases, minimize the utilization of fungicides, and improve the yield of cocoa production.…”
Section: Introductionmentioning
confidence: 99%
“…The typical symptoms include abnormal shoots that display stem swellings, bud proliferation, and vegetative brooms, which inspired the name witches’ broom disease in cocoa [ 5 ]. The results of recent studies from the major cocoa-producing provinces of Ecuador showed that Moniliophthora species possess high morphological and genetic diversity [ 6 , 7 , 8 , 9 ]. For this reason, some alternatives such as cacao agroforestry systems [ 1 ] and biological controls using products based on endophytic organisms, including the combined application of natural or chemical products [ 10 ], have been used to reduce the impact of diseases, minimize the utilization of fungicides, and improve the yield of cocoa production.…”
Section: Introductionmentioning
confidence: 99%